2018
DOI: 10.1159/000487030
|View full text |Cite
|
Sign up to set email alerts
|

LINC00037 Inhibits Proliferation of Renal Cell Carcinoma Cells in an Epidermal Growth Factor Receptor-Dependent Way

Abstract: Background/Aims: LINC00037 has previously been reported to be up-regulated in clear cell renal cell carcinoma (ccRCC), however, the underlying mechanism remained unknown. In this study, we designed to investigate the functional role of LINC00037 in ccRCC Methods: LINC00037 knockdown and re-expressing 786-O and A498 cells were established. CCK8 assay and EdU assay were performed to evaluate the proliferation rates of ccRCC cells. Flow cytometry assay was performed to detect the cell apoptosis and cell cycle. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(36 reference statements)
0
5
1
Order By: Relevance
“…For examples, the peptides encoded by noncoding gene DGCR5 showed significantly higher expression level in CCRCC compared to adjacent normal tissues ( Figure 3c). This contradicts the finding at RNA level where DGCR5 is ubiquitously expressed in normal tissues 11 . In Uterine Corpus Endometrial Carcinoma (UCEC), peptides detected from 5' UTR or non-canonical reading frame of protein coding genes, TSGA10, NPLOC4, MKKS and MUC1 were more abundant in tumors compared to normal tissues (Figure 3d).…”
Section: Differential Expressed Non-coding Gene Encoded Peptides Betwcontrasting
confidence: 77%
See 1 more Smart Citation
“…For examples, the peptides encoded by noncoding gene DGCR5 showed significantly higher expression level in CCRCC compared to adjacent normal tissues ( Figure 3c). This contradicts the finding at RNA level where DGCR5 is ubiquitously expressed in normal tissues 11 . In Uterine Corpus Endometrial Carcinoma (UCEC), peptides detected from 5' UTR or non-canonical reading frame of protein coding genes, TSGA10, NPLOC4, MKKS and MUC1 were more abundant in tumors compared to normal tissues (Figure 3d).…”
Section: Differential Expressed Non-coding Gene Encoded Peptides Betwcontrasting
confidence: 77%
“…For example, the non-coding RNA genes DGCR5 (DiGeorge Syndrome Critical Region Gene 5, located on chromosome 22q11), also known as LINC00037, were detected with ten unique peptides in clear cell renal cell carcinoma (CCRCC). Previous study by Gong et al reported DGCR5 is ubiquitously expressed in normal tissues, with much higher expression in CCRCC compared to normal kidney tissues 11 . Our analysis showed that DGCR5 probably encodes a functional protein product in CCRCC.…”
Section: Recurrent Detection Of Non-coding Gene Encoded Peptides In Dmentioning
confidence: 88%
“…ncRNA can be classified according to its length because of its different length. When ncRNA <200 nt is called shortchain ncRNA, ncRNA >200 nt, it is called long-chain ncRNA [25]. Neither long-chain ncRNA nor short-chain ncRNA can encode protein due to lack of ability to encode protein [26].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 25 µ g proteins in each lane were loaded for SDS-PAGE (10% gel) at 4°C. The concentrating voltage was 80 V and separating voltage was 110 V. The binding proteins were also identified by mass spectrometry to identify the potential binding proteins (H. Wayen Biotechnology, Shanghai, China) as previously described (21).…”
Section: Methodsmentioning
confidence: 99%